Analysis of Anemia Screening Policy Implementation for Pregnant Women in Tier I Healthcare Facilities: A Mixed-Methods Study in Urban-Rural Areas of South Tapanuli - Fatimah, Fatimah; Suryani, Elvi; Siregar, Rahmah Juliani; Harahap, Maryam Latifah (International Journal of Public Health Excellence (IJPHE), 2025)
Background: Anemia in pregnant women remains a significant public health issue in Indonesia, including in South Tapanuli. Anemia screening is a crucial policy for early detection and timely intervention, yet its implementation in primary healthcare facilities (Tier I) remains suboptimal. Objective: This study aims to analyze the implementation of anemia screening policies for pregnant women in Tier I healthcare facilities across urban-rural areas of South Tapanuli using a mixed-methods approach. Methods: The study employed a sequential explanatory mixed-methods design, combining quantitative data (a survey of 150 pregnant women and 30 healthcare workers) and qualitative data (in-depth interviews with 15 stakeholders, including health workers and policymakers). Quantitative data were analyzed using descriptive statistics, while qualitative data were examined using framework analysis. Results: Quantitatively, anemia screening coverage reached 68%, with disparities between urban (78%) and rural (58%) areas. Barriers included limited equipment, insufficient healthcare worker training, and low public awareness. Qualitative findings revealed issues in inter-stakeholder coordination, uneven budget allocation, and inadequate policy socialization. Conclusion: The implementation of anemia screening policies in South Tapanuli remains suboptimal, particularly in rural areas. Improvements in infrastructure, healthcare worker training, and culturally adapted community education are needed to enhance screening coverage.